Impact of Web 2.0 Technology Applications in Kerala University Library: Library Professionals’ Perspective - S. T., Seena; Pillai, Sudhier K. G. (DESIDOC Journal of Library & Information Technology, 2014)
The web has transformed the ways by which people search, find, use and communicate information. Integrating the use of web 2.0 technology into libraries has become the subject of interest among library professionals. Web 2.0 technologies facilitate interactive information sharing, interoperability, user centered design, dynamic content openness and user participation. Here an attempt has made to assess the Web 2.0 technology skills among library professionals in the University of Kerala. The questionnaire was the instrument used for data collection. Frequency count and simple percentage was used to analyze the questionnaire. The study reveals that email has an important impact on the level of web 2.0 use among library professionals. The majority of the library professionals do not have much idea about, RSS feeds, content management, social bookmarking, podcast, wikis, etc. The paper concludes that Kerala university library is in a developing stage in its infrastructure and use of ICT. Lack of proper planning and supervision and frequent change in infrastructure are the basic hurdles in successful development of ICT in university library. http://dx.doi.org/10.14429/djlit.34.6784